2006
DOI: 10.1111/j.1467-9450.2006.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of verbal interaction between interviewer and child in interviews with alleged victims of child sexual abuse

Abstract: A number (n = 27) of investigative interviews with children were analyzed with a view to explore the verbal dynamics between interviewer and child. Different types of interviewer utterances and child responses were defined, and the interrelationships between these were explored. The effectiveness of different interviewer utterances in eliciting information from children as well as the type of utterance the interviewer used to follow up an informative answer by the child were investigated. Option-posing and sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
129
3
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(146 citation statements)
references
References 28 publications
11
129
3
3
Order By: Relevance
“…Studies of interviewing practice in various parts of the United States, United Kingdom, Canada, Sweden, Scotland, Finland, Norway, and Israel consistently show that forensic interviewers use openended prompts quite rarely (e.g. Cederborg, La Rooy & Lamb, 2008;Korkman, Santtila, & Sandnabba, 2006;Lamb et al, 1996;Lamb et al, 2009;La Rooy, Lamb & Memon, 2011; What is alarming from a service perspective is that, in many studies, considerable expense and effort was directed to training interviewers, the interviewers seem to be well-aware of the recommended practices, and often believed that they were adhering to those recommendations. Research has thus revealed a disturbing dichotomy between 'knowledge about desirable practices' and 'the actual behavior of forensic investigators' (Lamb, Hershkowitz, Orbach, & Esplin, 2008).…”
Section: Forensic Interviewing Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of interviewing practice in various parts of the United States, United Kingdom, Canada, Sweden, Scotland, Finland, Norway, and Israel consistently show that forensic interviewers use openended prompts quite rarely (e.g. Cederborg, La Rooy & Lamb, 2008;Korkman, Santtila, & Sandnabba, 2006;Lamb et al, 1996;Lamb et al, 2009;La Rooy, Lamb & Memon, 2011; What is alarming from a service perspective is that, in many studies, considerable expense and effort was directed to training interviewers, the interviewers seem to be well-aware of the recommended practices, and often believed that they were adhering to those recommendations. Research has thus revealed a disturbing dichotomy between 'knowledge about desirable practices' and 'the actual behavior of forensic investigators' (Lamb, Hershkowitz, Orbach, & Esplin, 2008).…”
Section: Forensic Interviewing Researchmentioning
confidence: 99%
“…The answer, it seems, is that while it is relatively easy to conceptualize good interviewing practice and 'tell' interviewers what they should do, such guidelines do not translate automatically into practice. Research shows that interviewers require a substantial amount of regular support and feedback about the quality of their interviews for improvements in quality to be achieved and maintained (Lamb, Sternberg, Orbach, Esplin, & Mitchell, 2002a;Lamb, Sternberg, Orbach, Hershkowitz, Horowitz & Esplin, 2002b (Korkman, Santtila, Drzewiecki & Sandnabba, 2008;Korkman, Santtila & Sandnabba, 2006;Korkman, Santtila, Westeråker & Sandnabba, 2008;Santtila, Korkman & Sandnabba, 2004). National guidelines, introduced in 2003(Taskinen, 2003 …”
Section: Nichd Protocol Review 11mentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the evaluation research converges on the discouraging conclusion that investigative interviewers tend to use predominantly short-answer questions with few pauses and an excessive number of closed and leading questions (Cederborg, Orbach, Sternberg, & Lamb, 2000;Korkman, Santtila, & Sandnabba, 2006;Lamb et al, 1996;Mildren, 1997;Moston, Stephenson, & Williamson, 1993;Sternberg et al, 2001;Thoresen, Lønnum, Melinder, Stridbeck, & Magnussen, 2006). Furthermore, the pattern is widespread.…”
Section: Probing Memorymentioning
confidence: 99%
“…There has been an awareness in the last 15-20 years of the importance of following the evidence-based recommendations and that interviewers should be trained in accordance with best-practice recommendations; however, a growing body of field studies that have examined investigative interviews conducted in Israel (Hershkowitz et al 2005), the UK (Westcott and Kynan 2006), Australia (Agnew et al 2006;Guadagno and Powell, 2009), the USA , Canada (Cyr and Lamb 2009), Sweden (Cederborg et al 2000), Finland (Korkman et al 2006;Santtila et al 2004) and Norway (Johnson et al 2015) suggests that investigative interviewers generally fall short of capturing bestpractice evidence-based recommendations. In fact, regardless of country and investigative culture, the widespread tendency is for interviewers to rarely use open-ended questions that invite free narratives and instead rely heavily on option-posing, leading and suggestive prompts.…”
Section: Importance Of Interviewer Trainingmentioning
confidence: 99%